The Influence of Work Life Balance and Role Conflict on Employee Performance with Organizational Commitment as an Intervening Variable At BPJS Employment Northern Sumatra Region - Inggrid Maya Sari; Muhammad Isa Indrawan (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This study aims to analyze the effect of work life balance and role conflict on employee performance with organizational commitment as an intervening variable. This research was conducted at BPJS Employment in the Northern part of Sumatra. The population is 130 employees and the sample used is 98 using the Slovin formula. The research model uses path analysis and the measurement tool uses smart PLS version 3.3.3. The results of the research are Organizational Commitment which has a positive and insignificant effect on employee performance. Role Conflict has a Positive and Significant Effect on Employee Performance. Role Conflict has a Positive and Significant Effect on Organizational Commitment. Work Life Balance has a Positive and Significant Effect on Employee Performance. Work Life Balance has a Positive and Not Significant Effect on Organizational Commitment. Role Conflict has no significant positive effect on Employee Performance through Organizational Commitment. Work Life Balance has no significant positive effect on Employee Performance through Organizational Commitment.